Introduction to Natural Sciences: The Human Cultural History Perspective - Vysotskaya E.V; Lobanova A.D; Yanishevskaya M.A; Khrebtova S.B (Moscow State University of Psychology and Education, 2020)
We construct an introductory Natural Sciences curriculum that meets the demands of the «cultural-historical school». Our main task was to find the conditions that contribute to the formation of model mediation of text understanding within the Natural Sciences course, the content of which represents a purposeful transformation of natural materials in accordance with the cultural-historical specifics of human activity. To explore how schoolchildren acquire orienting functions of learning texts and models supporting the logical-genetic reconstruction of the natural scientific knowledge, we conducted an experimental teaching course in Natural Sciences for 2nd-graders (21 students, 102 academic hours). Our lessons proved a principal possibility of unfolding subject and model components of the course through the organization of joint actions consistent with the tasks of learning activity development in primary school children. Also, we assessed model-building skills in text understanding and task solving in children of two schools: the first group (103 students, 68 academic hours) studied the course we had developed, and the second group (80 students, 68 academic hours) received standard school courses. A significant improvement of model-building in the experimental group as compared to the control group suggests that cultural-activity-based introduction to Natural Sciences may have a certain potential in promoting the acquisition of orienting functions of learning models, which is vital for future advancement in middle and high school.